Relationship Between Attachment Style in Adulthood, Alexithymia, and Dissociation in Alcohol Use Disorder Inpatients. Mediational Model - Zdankiewicz-Ścigała, Elżbieta; Ścigała, Dawid Konrad (Frontiers in Psychology, 2018)
Background: An attachment theory has been conceptualized as an affect regulation theory, proposing that attachment is associated with the expression and recognition of emotions, as well as interpersonal functioning. Apart from these theoretical suggestions, there has been scarce empirical research on this subject-matter. Therefore, the objective of the present study was to investigate potential associations between attachment, alexithymia, and dissociation in substance use disorder inpatients. Methods: The Revised Adult Attachment Scale (RAAS), the Alexithymia Toronto Scale (TAS-20), the Michigan Alcoholism Screening Test (MAST), and the Curious Experiences Survey (CES) were administered to a sample of 97 substance use disorder inpatients recruited from drug and alcohol treatment centers in Warsaw, and 104 persons in control groups, Poland. Results: A comparative analysis between the group of alcohol addicts and non-addicts showed statistically significant differences related to: alexithymia, dissociation, and attachment styles. The analysis of models related to the impact of attachment styles on the level of alcohol addiction with regard to a mediatory role of alexithymia and dissociation showed that all models are well fitted to data and statistically significant: intimacy F(3.197)=34.41; p<0.001 and explains 34% (R2=0.3438); depend F(3.197)=36.55; p<0.001, and explains 36% (R2=0.3576); anxiety F(3.197)=34.71; p<0.001, and explains 35% (R2 =0.3458) of the variability of alcohol addiction scores. Alexithymia and dissociation enhance the fear of intimacy and rejection in a romantic relationship, contributing to emotional overload and stress regulated, among others, with stimulants. Conclusion: These findings support the broad attachment theory suggesting that attachment is associated with and predicts alexithymia and dissociation in the sample of substance use disorder inpatients. Alexithymia and dissociation, by inhibiting the processes of emotions’ identification and verbalization, cause that language does not serve for the purpose of changing self or others, as the communication is distorted. Absent are common meanings and accurate mutual understanding in a relationship.